REDUCING EPIGASTRIC PAIN SCALE OF DYSPEPSIA PATIENTS THROUGH THE CONSUMPTION OF TAPIOCA FLOUR (Manihot esculenta) AND TROPICAL FOREST HONEY: PRE-EXPERIMENTAL STUDY - Andri praja satria (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
A collection of signs and symptoms that are often felt by people with dyspepsia are epigastric pain, nausea, vomiting, satiety, and discomfort. Traditional medicine applied by the community includes the consumption of tapioca flour (Manihot esculenta) and tropical forest honey to reduce pain complaints caused by dyspepsia. To determine the effect of tapioca flour and tropical forest honey consumption (TFGFH) on the epigastric pain scale in dyspeptic patients. This quantitative study used a pre-experimental design with one group pretest-posttest. After the paired t-test was carried out, it was found that the significance value of p-value = 0.000 which means that there is a significant effect of TFGFH consumption on the epigastric pain scale in dyspeptic patients. There is a significant effect of TFGFH consumption on decreasing the epigastric pain scale in dyspeptic patients in the working area of ​​Sungai Siring Public Health Center, North Samarinda.